Liberal ethics in South Africa since 1948 : power, principle and responsible action - Godsell, R M (Department of Political Studies, 2015)
This dissertation examines a four part hypothesis: (a) that liberal ethics in South Africa, particularly since the victory of the (Afrikaner) National Party in 1948, have been characterised by a sense of political powerlessness; (b) that as a consequence of this powerlessness, these ethics have been more concerned with principle, motives, conscience and internal consistency than with the consequences of liberal action; (c) that this sense of powerlessness is not justified in the social and political environment of the 1980's; and therefore, (d) that liberals should review their ethical approach with a view to developing an ethic of responsible liberal action.